Profiles of muscle-specific oxygenation responses and thresholds during graded cycling incremental test - Sendra-Pérez, C.; Encarnacion-Martinez, A.; Salvador-Palmer, R.; Murias, J. M.; Priego-Quesada, J. I. (European Journal of Applied Physiology, 2024)
Compared to the determination of exercise thresholds based on systemic changes in blood lactate concentrations or gas exchange data, the determination of breakpoints based on muscle oxygen saturation offers a valid alternative to provide specific information on muscle-derived thresholds. Our study explored the profiles and timing of the second muscle oxygenation threshold (MOT2) in different muscles. Twenty-six cyclists and triathletes (15 male: age = 23 ± 7 years, height = 178 ± 5 cm, body mass = 70.2 ± 5.3 kg; 11 female: age = 22 ± 4 years, height = 164 ± 4 cm, body mass = 58.3 ± 8.1 kg) performed a graded exercise test (GXT), on a cycle ergometer. Power output, blood lactate concentration, heart rate, rating of perceived exertion, skinfolds and muscle oxygen saturation were registered in five muscles (vastus lateralis, biceps femoris, gastrocnemius medialis, tibialis anterior and triceps brachii) and percentage at which MOT2 occurred for each muscle was determinated using the Exponential Dmax. The results of Statistical Parametric Mapping and ANOVA showed that, although muscle oxygenation displayed different profiles in each muscle during a GXT, MOT2 occurred at a similar percentage of the GXT in each muscle (77% biceps femoris, 75% tibalis anterior, 76% gastrocnemius medialis and 72% vastus lateralis) and it was similar that systemic threshold (73% of the GXT). In conclusion, this study showed different profiles of muscle oxygen saturation in different muscles, but without notable differences in the timing for MOT2 and concordance with systemic threshold. Finally, we suggest the analysis of the whole signal and not to simplify it to a breakpoint.